Temporomandibular disorder therapy with splint stabilization - Riskani Djafri; Rustan Ambo Asse; Bahruddin Thalib (Indonesia Prosthodontic Association, 2023)
A 14-years-old female patient came to a hospital with a complaint of feeling swelling on the left cheek, the right jaw joint often made noises since 6 months ago. The patient had a motorcycle accident 2 years ago and hit his left cheek at the time of the accident. the patient is dizzy, nauseous, does not vomit. The patient was referred to the prosthodontics department. Bad habits in elementary school often biting a pencil, bruxism and quitting in 6th grade. Intraoral examination showed dental caries 46, with missing teeth 33 and 28, good oral hygiene, anterior deep bite, normal occlusion. A composite filling restoration of tooth 46, tooth scaling and making stabilization splints were performed to help reduce pain, to eliminate occlusal disharmony, prevent tooth wear and tear, reduce bruxism and parafunction, treat masticatory muscle dysfunction and change the TMJ structural relationship. Joint disorders are symptoms of pain in the joints or muscles of mastication, with or without jaw movement. An occlusal splint is a re-movable appliance made of acrylic, made according to the occlusal and incisal surfaces. Occlusal splints have been used to treat symptoms of bruxism and disorders of TMJ.